Barriers to condom use among key populations in Namibia. (December 2019) - Russell, Colin; Tahlil, Kadija; Davis, Margaret; Winston, Anna; Amaambo, Taimi; Hamunime, Ndapewa; Pietersen, Ismelda; Jordan, Michael R; Tang, Alice M; Hong, Steven Y
Key populations (KPs), particularly female sex workers (FSWs) and men who have sex with men (MSM), are at increased risk for HIV. Namibia is a global priority for HIV prevention interventions. Marginalized communities must be provided effective and culturally appropriate means to prevent HIV, namely condom use. This cross-sectional analysis of data collected by The Society for Family Health was conducted from 2016 to 2017 in Namibia. Demographics and consistent condom use (CCU) barriers were analyzed among 621 FSWs, MSM, and Other KPs. From the data, 37% FSWs, 24% MSM, and 28% Other KPs were HIV-positive. One-quarter of FSWs and Other KPs reported CCU, while 46% MSM reported CCU. Consistent condom users were more likely to be HIV-negative, have achieved a higher education and use condom-compatible lubricant (CCL). In a multivariate model, higher education, being HIV-negative, and always using CCL remained independent correlates of CCU. Substance use and condom unavailability were the most commonly identified barriers to CCU. FSWs reported client-focused reasons for not using condoms. To the best of our knowledge, this is the first peer-reviewed study assessing condom use behavior and associated factors among FSWs and MSM in Namibia.